2009
DOI: 10.1530/rep-08-0461
|View full text |Cite
|
Sign up to set email alerts
|

AKT (protein kinase B) is implicated in meiotic maturation of porcine oocytes

Abstract: The aim of this study was to investigate the involvement of the serine/threonine protein kinase AKT (also called protein kinase B) in the control of meiosis of porcine denuded oocytes (DOs) matured in vitro. Western blot analysis revealed that the two principal AKT phosphorylation sites, Ser473 and Thr308, are phosphorylated at different stages of meiosis. In freshly isolated germinal vesicle (GV)-stage DOs, Ser473 was already phosphorylated. After the onset of oocyte maturation, the intensity of the Ser473 ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 55 publications
5
45
0
Order By: Relevance
“…Thus, FSH-induced resumption of meiosis does not seem to be regulated by PI3K/AKT, but this pathway appears important for progression of meiosis to MI/MII stage. This observation is in agreement with previous studies in the pig (Shimada et al 1988, Kalous et al 2009). The mechanism of the interruption of meiosis may consist in increased activity of glycogen synthase kinase 3 in centrosomal region, which leads to formation of aberrant MI spindles (Kalous et al 2009).…”
Section: Signaling In Pig Cumulus-oocyte Complexessupporting
confidence: 94%
See 1 more Smart Citation
“…Thus, FSH-induced resumption of meiosis does not seem to be regulated by PI3K/AKT, but this pathway appears important for progression of meiosis to MI/MII stage. This observation is in agreement with previous studies in the pig (Shimada et al 1988, Kalous et al 2009). The mechanism of the interruption of meiosis may consist in increased activity of glycogen synthase kinase 3 in centrosomal region, which leads to formation of aberrant MI spindles (Kalous et al 2009).…”
Section: Signaling In Pig Cumulus-oocyte Complexessupporting
confidence: 94%
“…This observation is in agreement with previous studies in the pig (Shimada et al 1988, Kalous et al 2009). The mechanism of the interruption of meiosis may consist in increased activity of glycogen synthase kinase 3 in centrosomal region, which leads to formation of aberrant MI spindles (Kalous et al 2009). The AREG-stimulated resumption of oocyte maturation, however, seems to be dependent on PI3K/AKT activity in cumulus cells as shown in our study and also in another study carried out on the pig model .…”
Section: Signaling In Pig Cumulus-oocyte Complexessupporting
confidence: 94%
“…At the MII stage, Akt was reported to control PB2 emission and normal chromosomal alignment on microtubules (Hoshino & Sato 2008). Although Akt activity Hoshino & Sato (2008) and Cecconi et al (2010) Akt activity is not essential for induction of GBVD; however, it plays a substantial role during progression of meiosis to the MI/MII-stage Porcine oocytes Kalous et al (2009) Increased cAMP levels are necessary to maintain oocytes under meiotic arrest. PKA and Akt kinase phosphorylate PDE3A to enhance its enzymatic activity at the onset of oocyte maturation…”
Section: Pi3k/pten/akt and Tsc/mtor Pathways And Regulation Of Oocytmentioning
confidence: 99%
“…Mouse oocytes Romasko et al (2013) Blocking 4E-BP1 phosphorylation using Torin2, an active site mTOR inhibitor, during maturation of bovine oocytes results in arrest of up to 60% of oocytes in the MI stage Bovine oocytes Mayer et al (2014) Survivin, a downstream target protein of the PI3K/Akt and mTOR pathways, regulates proper meiotic spindle organization, spindle assembly checkpoint activity, timely metaphase-to-anaphase transition and cytokinesis Mouse oocytes Jiang et al (2014) has not been found to be essential for induction of GVBD in porcine oocytes, it plays a substantial role during progression of meiosis to MI/MII-stage (Kalous et al 2009). Similar studies on bovine oocytes have demonstrated the involvement of Akt in the regulation of the meiotic MI/MII transition (Tomek & Smiljakovic 2005).…”
Section: Pi3k/pten/akt and Tsc/mtor Pathways And Regulation Of Oocytmentioning
confidence: 99%
“…LH surge stimulates also PI3K/AKT (Han et al, 2006;Hoshino and Sato, 2008;Tomek and Smiljakovic, 2005). Akt activity increases during early steps of mouse oocyte maturation to activate either PDE3A (Han et al, 2006) or downstream mTOR pathway, which phosphorylates factors promoting protein synthesis (Kang and Han, 2011;Kalous et al, 2009). Suppression of Akt activity determines a significant decrease of CDK1 activity and delayed resumption of meiosis in mouse oocytes (Kalous et al, 2009).…”
Section: Akt Roles In Oocyte Maturation and In Preimplantation Embryosmentioning
confidence: 99%